Parallel Self-Tuning Fuzzy PD plus PD Controller for a Stewart-Gough Platform-Based Spatial Joystick - Omurlu, V. E.; Yildiz, I. (SPRINGER HEIDELBERG, 2012)
Stewart platform (SP) mechanisms have wide application area in aerospace and manufacturing industry with their nonlinear structure allowing spatial motion capabilities. Nonlinearities in the structure of the mechanism lead to complications in the dynamics of the system and result in complex control algorithms for dexterity in motion and force/torque feedback. This paper aims to represent stiffness control by means of independent joint self-tuning fuzzy-PD control algorithm on an experimental 3 x 3 SP parallel robotic mechanism, which will be used as a fly-by-wire flight control unit. Simulation model and experimental system responses are compared employing stiffness control for model verification. Following the selection of optimum control coefficients of self-tuning structure from the simulation model, responses are compared with alternative control algorithms like fuzzy PD, self-tuning fuzzy PD and PD controllers. Experimental system responses are also provided and the satisfactory performance of the proposed controller is observed.
Keywords: Parallel robots; Fuzzy control; Mechatronics; Flight control; DYNAMIC-ANALYSIS; Science & Technology - Other Topics